THE HISTORICAL ORIGIN OF MATHEMATICAL TERMS AND THEIR FUNCTIONING IN MODERN ENGLISH, RUSSIAN, AND UZBEK LANGUAGES - Nuridinova Dilnura Khamzaevna (International Journal of Literature and Language Studies, 2026)
The article examines the historical sources of the formation of mathematical terminology and analyzes the peculiarities of its functioning in modern English, Russian, and Uzbek. Despite the universality of the mathematical system, the linguistic representation of mathematical concepts has nationally specific features determined by the historical, cultural, and structural factors of each language’s development.